Molecular and Pharmacological Bladder Cancer Therapy Screening: Discovery of Clofarabine as a Highly Active Compound - Ertl, Iris E; Lemberger, Ursula; Ilijazi, Dafina; Hassler, Melanie R; Bruchbacher, Andreas; Brettner, Robert; Kronabitter, Hannah; Gutmann, Michael; Vician, Petra; Zeitler, Gerhard; Koren, Anna; Lardeau, Charles-Hugues; et al. (European urology, 2022)
BACKGROUND: The heterogeneity of bladder cancers (BCs) is a major challenge for the development of novel therapies. However, given the high rates of recurrence and/or treatment failure, the identification of effective therapeutic strategies is an urgent clinical need. OBJECTIVE: We aimed to establish a model system for drug identification/repurposing in order to identify novel therapies for the treatment of BC. DESIGN, SETTING, AND PARTICIPANTS: A collection of commercially available BC cell lines (n = 32) was comprehensively characterized. A panel of 23 cell lines, representing a broad spectrum of BC, was selected to perform a high-throughput drug screen. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Positive hits were defined as compounds giving >50% inhibition in at least one BC cell line. RESULTS AND LIMITATIONS: Amongst >1700 tested chemical compounds, a total of 471 substances exhibited antineoplastic effects. Clofarabine, an antimetabolite drug used as third-line treatment for childhood acute lymphoblastic leukaemia, was amongst the limited number of drugs with inhibitory effects on cell lines of all intrinsic subtypes. We, thus, reassessed the substance and confirmed its inhibitory effects on commercially available cell lines and patient-derived cell cultures representing various disease stages, intrinsic subtypes, and histologic variants. To verify these effects in vivo, a patient-derived cell xenograft model for urothelial carcinoma (UC) was used. Well-tolerated doses of clofarabine induced complete remission in all treated animals (n = 12) suffering from both early- and late-stage disease. We further took advantage of another patient-derived cell xenograft model originating from the rare disease entity sarcomatoid carcinoma (SaC). Similarly to UC xenograft mice, clofarabine induced subcomplete to complete tumour remissions in all treated animals (n = 8). CONCLUSIONS: The potent effects of clofarabine in vitro and in vivo suggest that our findings may be of high clinical relevance. Clinical trials are needed to assess the value of clofarabine in improving BC patient care. PATIENT SUMMARY: We used commercially available cell lines for the identification of novel drugs for the treatment of bladder cancer. We confirmed the effects of one of these drugs, clofarabine, in patient-derived cell lines and two different mouse models, thereby demonstrating a potential clinical relevance of this substance in bladder cancer treatment.
Keywords: myši; klofarabin; Urinary Bladder Neoplasms; Early Detection of Cancer; Carcinoma, Transitional Cell; Clofarabine; karcinom z přechodných buněk; zvířata; nádory močového měchýře; Mice; Animals; lidé; Precursor Cell Lymphoblastic Leukemia-Lymphoma; akutní lymfatická leukemie; Humans; časná detekce nádoru